2015
DOI: 10.18092/ijeas.14404
|View full text |Cite
|
Sign up to set email alerts
|

Turi̇zm Geli̇rleri̇ne Yöneli̇k Bi̇r Yakinsama Anali̇zi̇

Abstract: ÖZBu çalıĢmanın amacı, Türkiye'nin uluslararası turizm sektöründe hem en yakın rakipleri olan hem de Türkiye'nin de içerisinde yer aldığı dünyanın en geliĢmiĢ dokuz turizm ekonomisi ile Türkiye arasında herhangi bir yakınsama sürecinin olup olmadığını araĢtırmak ve turizm ekonomisi anlamında turizmyakınsama iliĢkisini ortaya koymaktır. Bu bağlamda; 1995-2009 dönemini kapsayan bir panel veri seti oluĢturulmuĢ ve söz konusu ülkelerin turist sayısı baĢına düĢen turizm gelirlerinin yakınsaması Panel Birim Kök anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…According to the study's findings, the authors concluded that there is convergence in 10 of the 14 markets and no convergence in the other four markets. Bozkurt and Bahar (2015) conducted a convergence test with Panel unit root analysis with data from the world's most developed nine tourism economies, including Turkey, from 1995-2009. According to the findings they obtained from the study, they concluded that Turkey is in the process of convergence with the USA, France, Spain, and China.…”
Section: Related Literaturementioning
confidence: 99%
“…According to the study's findings, the authors concluded that there is convergence in 10 of the 14 markets and no convergence in the other four markets. Bozkurt and Bahar (2015) conducted a convergence test with Panel unit root analysis with data from the world's most developed nine tourism economies, including Turkey, from 1995-2009. According to the findings they obtained from the study, they concluded that Turkey is in the process of convergence with the USA, France, Spain, and China.…”
Section: Related Literaturementioning
confidence: 99%